Legal Analysis of Chemical Castration on the Crime of Sexual Violence against Children - Khairunnisa, Devi Meilina; Gusthomi, Moh. Imam; Deka Maghfira, M. Risyah Farras; Saputra, Andhika (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
There are many cases of sexual abuse of children in Indonesia. The softness of the law against the perpetrators has made this case quite fertile. The presence of chemical castration sanctions, rehabilitation, and also the installation of detection devices are considered very light and not worth the act of destroying the child's future. This study uses a qualitative descriptive research method that aims to determine the effect of the castration law on perpetrators of sexual abuse. The result is that the chemical castration law is still not sufficient to have a fearful effect on potential perpetrators and a deterrent effect on perpetrators considering that the term is only two years. There are legal options such as life imprisonment, permanent castration, and the death penalty. However, two of them must intersect with the existence of human rights. However, life imprisonment can be the right choice to be applied to break the chain of sexual crimes against children.